Longitudinal Associations between Posttraumatic Stress Disorder Severity and Personality Disorder Features among Female Rape Survivors - Bovin, Michelle J.; Wolf, Erika J.; Resick, Patricia A. (Frontiers in Psychiatry, 2017)
This study evaluated how change in posttraumatic stress disorder (PTSD) symptoms was associated with residualized change in comorbid personality disorder (PD) features and vice versa over the course of 5-10 years. The sample was comprised of 79 female rape survivors who met criteria for PTSD and who were a part of a larger study examining the effects of trauma-focused therapy. PTSD was assessed with the DSM-IV version of the Clinician Administered PTSD Scale (CAPS-IV; Blake et al., 1995) and PD features were assessed with the DSM-IV dimensional PD scales on the Schedule for Nonadaptive and Adaptive Personality (SNAP; Clark, 1996). PTSD symptom severity and PD features were assessed at baseline and between 5-10 years after completing treatment. Multiple regression analyses revealed that PTSD symptom change was related to residualized change in PD severity for paranoid, schizotypal, antisocial, borderline, avoidant, and dependent PD (βs ranged from -.23 to -.33; all ps < .05). In addition, for borderline and antisocial PDs, longitudinal stability of the PD was attenuated among those with greater PTSD symptom improvement (i.e., the relationship between these PDs over time was altered as a function of PTSD symptom change; βs ranged from -.27 to -.29; all ps < .05). Similarly, change in severity of paranoid, schizotypal, antisocial, avoidant, and obsessive compulsive PD was associated with residualized change in PTSD symptoms (βs ranged from -.32 to -.41; all ps < .05), and the longitudinal stability of PTSD was attenuated as a product of change in obsessive compulsive PD (β = -.27; p < .02). These findings suggest that these two sets of disorders may impact one another substantially, altering the course of even chronic, characterological conditions. This carries important clinical implications for the treatment of both PTSD and PDs.